Pengaruh yang terdiri dari Current Ratio (CR) Quick Ratio (QC), Gross Profit Margin (GPM), Operating Profit Margin (OPM) terhadap Harga Saham pada Perusahaan sektor Konsumsi yang terdaftar di Bursa Efek Indonesia Periode 2014-2016 - Komsatun (Universitas Ngudi Waluyo, 2020)
The purpose of this study is to examine the effect of Current Ratio (CR), Quick Ratio (QC), Gross Profit Margin (GPM), Operating Profit Margin (OPM) on Share Prices in Consumption sector companies listed on the Indonesia Stock Exchange in the year period 2014-2016. The purposive sampling technique was used to obtain a sample size of 22 companies or 66 data in three years. To analyze the hypothesis of this study using multiple linear regression with SPSS Version 21. The results showed that the Current Ratio (CR) and Gross Profit Margin (GPM) had no significant effect on stock prices, while the Quick Ratio (CR) and Operating Profit Margin (OPM) significant and significant effect on stock prices.